2018
DOI: 10.1016/j.clbc.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy Dose Intensity and Overall Survival Among Patients With Advanced Breast or Ovarian Cancer

Abstract: Dose delays, dose reductions, and reduced RDI were common. In advanced breast cancer, health status and triple-negative disease were significantly associated with mortality. In advanced ovarian cancer, dose reductions and tumor histology were significantly associated with mortality. These results can help identify potential risk factors and characterize the effect of chemotherapy dose modification strategies on mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 21 publications
3
54
1
4
Order By: Relevance
“…Recent studies suggest that relative intensity dose is more relevant than the time to complete chemotherapy schemes, although there is conflicting evidence 57 . A recent, large meta‐analysis found that increasing the dose intensity of adjuvant chemotherapy by shortening the interval between treatment cycles, or by giving individual drugs sequentially rather than giving the same drugs concurrently, moderately reduced the 10‐year risk of recurrence and death from breast cancer without increasing mortality from other causes 58 …”
Section: Breast Health System Requirementsmentioning
confidence: 99%
“…Recent studies suggest that relative intensity dose is more relevant than the time to complete chemotherapy schemes, although there is conflicting evidence 57 . A recent, large meta‐analysis found that increasing the dose intensity of adjuvant chemotherapy by shortening the interval between treatment cycles, or by giving individual drugs sequentially rather than giving the same drugs concurrently, moderately reduced the 10‐year risk of recurrence and death from breast cancer without increasing mortality from other causes 58 …”
Section: Breast Health System Requirementsmentioning
confidence: 99%
“…For instance, for six cycles of tri-weekly paclitaxel and carboplatin therapy, if COVID-19 causes a 4week delay during treatment, the relative dose intensity will be approximately 82%. The relationship between the relative dose intensity and prognosis has been described for various cancer types [4][5][6][7][8][9]. Even if treatment is deferred, it is not desirable for treatment to be postponed unnecessarily.…”
Section: Difficulty In Deciding Whether To Postpone Treatmentmentioning
confidence: 99%
“…Breast cancer is extensively heterogenous in pathological feature and molecular profiling, and therefore treatment regimen for each patient [ 2 , 3 ]. Generally, surgical removal and chemotherapy are widely used in the clinical management of patients with breast cancer [ 4 ]. Patients with estrogen receptor- (ER-) positive are treated with adjuvant endocrine therapy such as tamoxifen, and patients with human epidermal growth factor receptor 2- (HER2-) positive are treated with adjuvant targeted therapy such as herceptin [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%